Perspectives of the California community colleges historically Black colleges and universities transfer guarantee program - McGee, Tynisha Nicole (Kansas State University, 2024)
The purpose of this study was to explore constituent perspectives of the California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program. The researcher queried representatives from participating community colleges and Historically Black Colleges and Universities regarding their perspectives of the program. The California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program's goal is to educate students about additional transfer opportunities at these institutions and develop pathways that will ultimately increase baccalaureate degree attainment. The conceptual framework guiding this study was the 2013 Hanover Research Report on Strategies for Recruiting Community College Transfer Students. In this seminal report, the 2013 Hanover Research Report on Strategies for Recruiting Community College Transfer Students presented best practices for recruiting and marketing to community college transfer students, including information on credit evaluation policies at several four‐year institutions. A qualitative research method was used to conduct this study. Three central research questions guided this study: 1. How do participants describe the California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program in providing California Community College students additional transfer opportunities at HBCUs? 2. How do participants describe the California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program in developing pathways to increase baccalaureate degree attainment? 3. How did participants' descriptions of the California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program align with the recommended practices in the 2013 Hanover Research Report on Strategies for Recruiting Community College Transfer Students? The findings from this study revealed that the participants described the California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program as having streamlined the transfer process and expanded transfer options. The participant's description of the program emphasized the program's contribution to increasing degree attainment through streamlined pathways and support systems. The participants also expressed doubts about the program’s effectiveness in addressing barriers to degree completion. The analysis of participants' descriptions of the transfer practices at participating intuitions revealed alignment with the 2013 Hanover Research Report on Strategies for Recruiting Community College Transfer Students. The researcher proposed several recommendations: conduct a quantitative study focusing on a larger population of participants, conduct training for counselors participating in the program, and further investigate baccalaureate degree attainment.
Keywords: Community college; Historically Black Colleges and Universities; Transfer; California Community Colleges Historically Black Colleges and Universities Transfer Guarantee Program; Community college transfer to Historically Black Colleges and Universities; Perspectives